Therapeutic alternatives for sporotrichosis induced by wild-type and non-wild-type Sporothrix schenckii through in vitro and in vivo assessment of enilconazole, isavuconazole, posaconazole, and terbinafine - Vasurom Aroonvuthiphong; Norasuthi Bangphoomi (Scientific Reports)
Abstract This study explores the effectiveness of various antifungal drugs in treating sporotrichosis caused by Sporothrix schenckii, especially in non-wild-type (non-WT) strains. The drugs tested include enilconazole (ENIL), isavuconazole (ISA), posaconazole (POS), terbinafine (TER), and itraconazole (ITC). The study involved in vitro and in vivo tests on 10 WT isolates and eight ITC non-WT isolates. Two isolates were assessed using time-kill assays, checkerboard assays, and Galleria mellonella infection models. In vitro studies have shown that all of these drugs were more effective than or equal to ITC against WT and non-WT isolates. No ITC resistance was observed with other azoles. All drugs inhibited fungal growth of WT and non-WT strains within 24 h at all incubations. ENIL and TER showed fungicidal effect against types at over 2x minimum inhibitory concentrations with no regrowth. POS was fungicidal against WT at high concentrations but not against non-WT. ISA was only fungicidal for non-WT. ITC did not exhibit any fungicidal activity. In checkerboard experiments, the combination of POS or ISA with TER showed enhanced activity against WT and non-WT strains, surpassing the combination of ITC with TER. In vivo model experiments demonstrated significantly reduced mortality rates with ENIL, POS, and TER against WT and with ENIL, ISA, POS, and TER against non-WT. The study concludes that monotherapy with ENIL, ISA, POS, and TER, and combinations of POS/TER or ISA/TER, show promise as effective antifungal treatments against S. schenckii, including ITC-non-WT isolates.